Common feedstocks of late accretion for the terrestrial planets - Zhu, Meng-Hua; Morbidelli, Alessandro; Neumann, Wladimir; Yin, Qing-Zhu; Day, James M. D.; Rubie, David C.; Archer, Gregory J.; Artemieva, Natalia; Becker, Harry; Wünnemann, Kai (Nature astronomy, 2021)
Abundances of the highly siderophile elements (HSEs) in silicate portions of Earth and the Moon provide constraints on the impact flux to both bodies, but only since ~100 Myr after the beginning of the Solar System (hereafter tCAI). The earlier impact flux to the inner Solar System remains poorly constrained. The former dwarf planet Vesta offers the possibility to probe this early history, because it underwent rapid core formation ~1 Myr after tCAI and its silicate portions possess elevated chondritic HSE abundances. Here we quantify the material accreted into Vesta’s mantle and crust and find that the HSE abundances can only be explained by the bombardments of planetesimals from the terrestrial planet region. The Vestan mantle accreted HSEs within the first 60 Myr; its crust accreted HSEs throughout the Solar System history, with asteroid impacts dominating only since ~4.1 billion years ago. Our results indicate that all major bodies in the inner Solar System accreted planetesimals predominantly from the terrestrial planet region. The asteroid belt was either never significantly more massive than today, or it rapidly lost most of its mass early in the Solar System history.
Gesehen am 03.01.2023